Representasi Komunikasi Efektif antara Orang Tua dan Anak di Media Sosial: Analisis pada Akun Tiktok @Shabiraalula&Ayah - Mita Mita; Ilah Holilah (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2025)
Effective communication between parents and children is a key element in establishing a harmonious, understanding, and supportive family relationship. In the digital era, social media has become an integral part of daily life, including within family communication dynamics. TikTok, as one of the most popular social media platforms, serves not only as a source of entertainment but also as a medium for building and displaying interpersonal relationships, including those between parents and their children. This study aims to explore how effective communication between parent and child is represented through the TikTok account @Shabiraalula&Ayah. Using a descriptive qualitative approach, this research analyzes various video content featuring father-daughter interactions to identify forms of communication present in their exchanges. The findings reveal that the communication displayed is characterized by openness, expressions of affection, humor, emotional support, and active engagement from both sides. The relationship portrayed in these videos reflects a healthy and balanced communication pattern that can serve as a positive example for a wider audience. Furthermore, social media proves to be a potential space for strengthening family bonds and promoting positive parenting messages. These findings emphasize that the wise use of social media can contribute to improving family relationships, especially between parents and children.